Porous Microneedle Patch for Electroosmosis‐Promoted Transdermal Delivery of Drugs and Vaccines. Issue 1 (10th October 2021) - Abe, Hiroya; Sato, Kaito; Kimura, Natsumi; Kusama, Shinya; Inoue, Daisuke; Yamasaki, Kenshi; Nishizawa, Matsuhiko
Abstract : A charged porous microneedle (PMN) generates the electroosmotic flow (EOF) and promotes the through‐needle transport of molecules and particles, indicating its applicability for the EOF‐based low‐invasive transdermal delivery of drugs and vaccines. The negatively charged PMN is prepared by grafting a thin film of poly (2‐acrylamido‐2‐methylpropanesulfonic acid) (PAMPS) onto the inner wall of the microchannels of the polyglycidyl methacrylate PMN. Promoted transport from anode to cathode is observed for albumin, Au nanoparticles (15, 50 nm), and silica beads (100 nm), indicating the generation of an EOF strong enough to transport these negatively charged larger size species against their electrophoretic motion. A model antigen ovalbumin (OVA) is preloaded in the PMN, and is injected to a hydrogel and a pig skin with a higher efficiency (more than 2 times) than the conventional diffusion‐based passive release. These results successfully demonstrate the novel EOF‐based effective injection of drugs and vaccines into the skin, achieved by the newly developed charged PMN. Abstract : A porous microneedle array modified by a thin charged polymer film generates an electroosmotic flow that promotes the through‐needle transport of molecules and particles, indicating its applicability for low‐invasive transdermal delivery of drugs and vaccines.